Multidisciplinary management of cardiovascular disease in women: Delphi consensus - Gámez, José M.; Pedreira Pérez, Milagros; Fernández Olmo, María Rosa; Fasero Laiz, María; Inaraja, Verónica; Pallarés Carratalá, Vicente (Frontiers in Cardiovascular Medicine, 2024)
Background Current clinical guidelines on cardiovascular disease (CVD) do not specifically address the female population. The aim of this consensus is to know the opinion of a group of experts on the management of CVD in women. Methods Through a Delphi consensus, 31 experts in cardiology, 9 in gynecology and obstetrics, and 14 primary care physicians, showed their degree of agreement on 44 items on CVD in women divided into the following groups: (1) risk factors and prevention strategies; (2) diagnosis and clinical manifestations; and (3) treatment and follow-up. Results After two rounds, consensus in agreement was reached on 27 items (61.4%). Most of the non-consensus items (31.8%) belonged to group 3. The lack of consensus in this group was mainly among gynecologists and primary care physicians. The panelists agreed on periodic blood pressure control during pregnancy and delivery to detect hypertensive disorders, especially in women with a history of preeclampsia and/or gestational hypertension, and diabetes mellitus control in those with gestational diabetes. Also, the panelists agreed that women receive statins at a lower intensity than men, although there was no consensus as to whether the efficacy of drug treatments differs between women and men. Conclusions The high degree of consensus shows that the panelists are aware of the differences that exist between men and women in the management of CVD and the need to propose interventions to reduce this inequality. The low level of consensus reveals the lack of knowledge, and the need for information and training on this topic.